Habitual glucosamine use, APOE genotypes, and risk of incident cause-specific dementia in the older population - Chun Zhou; Yanjun Zhang; Sisi Yang; Ziliang Ye; Qimeng Wu; Mengyi Liu; Panpan He; Yuanyuan Zhang; Xianhui Qin (Alzheimer’s Research & Therapy, 2023)
Abstract Background The relationship of glucosamine use with incident dementia in the older population remains uncertain. We aimed to evaluate the longitudinal association between habitual glucosamine supplement and the risk of cause-specific dementia and examine the possible effect modifiers on this association. Methods The study included 214,945 participants over the age of 60 who had available information on glucosamine use and did not have dementia at baseline in the UK Biobank. The APOE genotypes were determined by a combination variant of rs429358 and rs7412. The primary outcome was incident vascular dementia, incident Alzheimer’s disease, and incident frontotemporal dementia, respectively. Results Over a median follow-up duration of 12 years, 1039, 1774, and 122 participants developed vascular dementia, Alzheimer’s disease, and frontotemporal dementia, respectively. Overall, habitual glucosamine use was significantly associated with a lower risk of incident vascular dementia (adjusted HR, 0.82; 95%CI, 0.70–0.96), but not significantly associated with incident Alzheimer’s disease (adjusted HR, 1.02; 95%CI, 0.92–1.14) and incident frontotemporal dementia (adjusted HR, 0.95; 95%CI, 0.63–1.43). Moreover, the inverse association between habitual glucosamine use and incident vascular dementia was more pronounced in participants with concomitant supplement of calcium (P-interaction = 0.011), and those without concomitant supplement of zinc (P-interaction = 0.018). However, APOE ε4 dosage and baseline cognitive function did not significantly modify the relationships of glucosamine use with incident vascular dementia or Alzheimer’s disease (All P-interactions > 0.05). Conclusions Regardless of APOE genotypes and baseline cognitive function, habitual glucosamine use was significantly inversely associated with incident vascular dementia in the older population.